53‐3: Invited Paper: Negative Dispersion Compensation Film using Self‐organization of Smectic Host and Guest Reactive Mesogen Molecules. Issue 1 (May 2017) - Lee, Ji-Hoon; Jeong, Kwang-Un
Abstract : We fabricated a compensation film with a negative dispersion (ND) of birefringence using a self‐organization of smectic host and guest reactive mesogen (RM) molecules. The host smectic reactive RM absorbing a shorter wavelength of light formed a layered‐structure and the guest molecules absorbing a longer wavelength of light were intersticed at the inter‐layer space of the layers. The ordinary refractive index of the guest was more rapidly decreased and consequently, the ND of birefringence was shown.